BANKRUPTCY PREDICTION BASED ON ALTMAN Z SCORE, SPRINGATE, AND ZMIJEWSKI METHODS IN RETAIL SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2014-2018 - Yohanni, Odilia; Dwi Setiani; Yunita Indah Pratiwi (Cirebon International Conference on Education and Economics Proceeding, 2024)
This aims to determine liquidation estimates using the Altman Z-Score, Springate and Zmijewski strategies in retail subsector companies listed on the Indonesia Stock Exchange 2014-2018. The question regarding the strategy used is a quantitative strategy. The information used is in the form of financial statements of each company. The testing procedure for this reflection is to use a Purposive sampling Testing procedure by testing 9 companies. The results obtained from this study are that in the altman Z-Score method, there are 4 companies that are predicted to facing bankruptcy, 1 company is estimated to be in the bankruptcy-prone zone and 4 companies are estimated to be safe from bankruptcy. The Altman Z-Score strategy has an accuracy rate of 56%. In the Springate method, there are 7 companies that are anticipated to experience bankruptcy and 2 companies are anticipated not to encounter bankruptcy. The Springate strategy has a precision rate of 22%. And finally in the Zmijewski method there are 5 companies predicted to be healthy and 4 companies predicted to experience bankruptcy, this method has a precision rate of 56%, so the Zmijewski method and the Altman Z-Score strategy have the same level of accuracy.